(3TQM GdCRgQjI aj Yde GdYQHjIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3GdeOQSI GdYeQjIs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bO SCdfj ef CYJbO UdGMg hdG jSYfj eNGdaJg Cf CTQM ebOeJj GdCRgQjI aj Yde GdYQHjI GdJj CedjJgG dHYV GdWdHI TQMG dWjaG aCLHJg Edi Pdc (B....s
(3BNQgG (B:s
.... (3aj UOhQ LGQ heLQhQ eJYdb HjhShS hGdfGS eYWha Ydi GdLfI haj gPG GdbOQ caGjI ddeHJOjA (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/297s
(3cTa GdXfhf dMGLj NdjaI (B2/1798s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs